Transcriptome and microRNA Sequencing Identified miRNAs and Target Genes in Different Developmental Stages of the Vascular Cambium in Cryptomeria fortunei Hooibrenk - Hu, Hailiang; Guo, Zhenhao; Yang, Junjie; Cui, Jiebing; Zhang, Yingting; Xu, Jin (Frontiers in Plant Science, 2021)
Cryptomeria fortunei Hooibrenk is an important coniferous fast-growing timber species and is widely used in landscaping. Recently, research on timber quality has gained much attentionin the field of tree breeding. Wood is the secondary xylem formed by the continuous inward division and differentiation of the vascular cambium; therefore, the development of the vascular cambium is particularly important for wood quality. In this study, we performed transcriptome analysis of different developmental stages of the cambial zone in C. fortunei using Illumina HiSeq sequencing, focusing on the general transcriptome and microRNA (miRNA) data. We performed functional annotation of the differentially expressed genes (DEGs) in the different stages identified by transcriptome sequencing and generated 15 miRNA libraries yielding 4.73 Gb clean reads. The most common length of the filtered miRNAs was 21 nt, accounting for 33.1% of the total filtered reads. We annotated a total of 32 known miRNA families. Some miRNAshad roles in hormone signal transduction (miR159, miR160 andmiR166), growth and development (miR166, miR396) and the coercion response (miR394, miR395), and degradome sequencing showed potential cleavage sites between miRNAs and target genes. Differential expression of miRNAs and target genes, functional validation of the obtained transcriptome and miRNA data provide a theoretical basis for further elucidating the molecular mechanisms of cellular growth and differentiation, as well as wood formation in the vascular cambium, which will help improve the wood quality of C. fortunei.